Ethnic-racial diversity, equity, and inclusion in the Brazilian corporate workplace - Vieira, Sofia de Freitas Santiago (2024)
The agenda of diversity has been growing, influenced by increasing awareness of socioeconomic inequalities globally. Particularly impacted by the murder of George Floyd in 2020 in the United States, the ethnic-racial aspect of diversity, equity, and inclusion (DEI) has gained strength, with corporations making strong commitments to fight racial discrimination. This global commotion has also impacted the Brazilian environment, which has deep and particular issues regarding race. The present dissertation has as its main objective identifying the main challenges and best practices executives have been facing in the pursuit of racial equity within the Brazilian corporate workplace. Based on targeted issues, this study proposes a structure which may collaborate for institutions to organize action plans to fight racial discrimination. Literature explores the particularities of the Brazilian environment and studies of challenges which encompass the black employee journey from the moment of recruitment onward and the necessary adaptations of the corporate workplace. By conducting semi-structured interviews with fourteen executives and researchers who are dealing with DEI in their work (and personal) lives, this dissertation combined academic foundations with empirical evidence to propose a structure corporations can use to organize their efforts to fight discrimination. The proposed structure is defined by the mapped challenges and best practices, which were identified from the recruitment stage to retention and belonging considerations, communication, adequately addressing racial issues, investment, and diversity management. Then, it suggests internal and external actions which can be seen as a starting point to action, addressing common misconceptions, and bypassing constraints often mentioned by businesses in this agenda. Aligned with corporate strategy and collaborative efforts, these initiatives can lead to sustainable transformation of organizations, basing themselves in business foundations.